2016
DOI: 10.1002/2016jb012886
|View full text |Cite
|
Sign up to set email alerts
|

Structural asperity focusing locking and earthquake slip along the Nicoya megathrust, Costa Rica

Abstract: On 5 September 2012, a moment magnitude 7.6 earthquake occurred along the locked megathrust interface directly beneath the Nicoya Peninsula in Costa Rica. The event was anticipated given the history of frequent large earthquakes and recent GPS results. Strain accumulation observed before and coseismic slip observed during the earthquake create a novel and important data set, offering a unique look at the strain and locking behavior around a large megathrust environment. Given this geodetic data, and a newly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 52 publications
(130 reference statements)
1
41
0
Order By: Relevance
“…This approach has brought much insight into the rheology of plate boundaries at subduction zones (e.g., Hu et al, 2014Hu et al, , 2016Klein et al, 2016;Kyriakopoulos & Newman, 2016;Masterlark, 2003;Wang, 2007), transform boundaries (e.g., Allison & Dunham, 2018;Freed & Bürgmann, 2004;Masterlark & Wang, 2002;Takeuchi & Fialko, 2013), and collision zones (Castaldo et al, 2017;Cattin & Avouac, 2000;C. This approach has brought much insight into the rheology of plate boundaries at subduction zones (e.g., Hu et al, 2014Hu et al, , 2016Klein et al, 2016;Kyriakopoulos & Newman, 2016;Masterlark, 2003;Wang, 2007), transform boundaries (e.g., Allison & Dunham, 2018;Freed & Bürgmann, 2004;Masterlark & Wang, 2002;Takeuchi & Fialko, 2013), and collision zones (Castaldo et al, 2017;Cattin & Avouac, 2000;C.…”
Section: Subduction Dynamics With the Integral Methodsmentioning
confidence: 99%
“…This approach has brought much insight into the rheology of plate boundaries at subduction zones (e.g., Hu et al, 2014Hu et al, , 2016Klein et al, 2016;Kyriakopoulos & Newman, 2016;Masterlark, 2003;Wang, 2007), transform boundaries (e.g., Allison & Dunham, 2018;Freed & Bürgmann, 2004;Masterlark & Wang, 2002;Takeuchi & Fialko, 2013), and collision zones (Castaldo et al, 2017;Cattin & Avouac, 2000;C. This approach has brought much insight into the rheology of plate boundaries at subduction zones (e.g., Hu et al, 2014Hu et al, , 2016Klein et al, 2016;Kyriakopoulos & Newman, 2016;Masterlark, 2003;Wang, 2007), transform boundaries (e.g., Allison & Dunham, 2018;Freed & Bürgmann, 2004;Masterlark & Wang, 2002;Takeuchi & Fialko, 2013), and collision zones (Castaldo et al, 2017;Cattin & Avouac, 2000;C.…”
Section: Subduction Dynamics With the Integral Methodsmentioning
confidence: 99%
“…Global studies have shown that large earthquakes (M W ≥ 7.5) preferably occur along a smooth subduction interface and that rough subducting seafloor is associated with lower seismic coupling and a creep-like behavior (Bassett & Watts, 2015;Lallemand et al, 2018;van Rijsingen et al, 2018;Wang & Bilek, 2014). In some places, geodetic measurements above subducting features show a local increase in interplate coupling (Collot et al, 2017;Kyriakopoulos & Newman, 2016), while in other places subducting topography is thought to cause a local decrease in coupling (Geersen et al, 2015;Marcaillou et al, 2016;Mochizuki et al, 2008;Singh et al, 2011). Following the classification of Lallemand et al (2018), which is based on the seafloor characteristics prior-to-subduction, Izu-Bonin-Mariana is considered almost entirely rough, while Japan-Kuril-Kamchatka is dominantly smooth.…”
Section: Comparison With Natural Observationsmentioning
confidence: 99%
“…As anticipated, the Nicoya earthquake ruptured a seismic gap beneath the Nicoya Peninsula that locked up following a M 7.7 event in 1950 and exhibiting an apparent 50–60 year recurrence of M w 7.0+ earthquakes along the megathrust [ Protti et al ., ]. After nucleating immediately offshore [ Yue et al ., ], the Nicoya earthquake ruptured primarily under the peninsula with up to 4 m of trenchward thrust in an area that was previously mapped as locked [ Feng et al ., ; Protti et al ., ; Kyriakopoulos and Newman , ]. Local foreshocks were observed 35 min prior to the main shock within 15 km of its hypocenter, which occurred within the same 30 km diameter zone as those remotely triggered by the 27 August 2012 M w 7.3 El Salvador event about 450 km to the northwest [ Walter et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…[] derived a new structural model for the subduction zone interface along the Middle America Trench. This plate geometry model was further used to reevaluate the interseismic locking and coseismic slip [ Kyriakopoulos and Newman , ] and image afterslip both updip of the dominant coseismic slip area and downdip to deep slow‐slip events previously identified [ Hobbs et al ., ].…”
Section: Introductionmentioning
confidence: 99%